2020
DOI: 10.3390/ijms21051580
|View full text |Cite
|
Sign up to set email alerts
|

Disparity between Inter-Patient Molecular Heterogeneity and Repertoires of Target Drugs Used for Different Types of Cancer in Clinical Oncology

Abstract: Inter-patient molecular heterogeneity is the major declared driver of an expanding variety of anticancer drugs and personalizing their prescriptions. Here, we compared interpatient molecular heterogeneities of tumors and repertoires of drugs or their molecular targets currently in use in clinical oncology. We estimated molecular heterogeneity using genomic (whole exome sequencing) and transcriptomic (RNA sequencing) data for 4890 tumors taken from The Cancer Genome Atlas database. For thirteen major cancer typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 73 publications
1
20
0
2
Order By: Relevance
“…Also, quality measuring of hierarchical clustering was applied to CGGA datasets for the same goal. This was performed by the Watermelon multisection method [33] that returns WM metric which positively reflects the quality of clustering of samples into pre-defined groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, quality measuring of hierarchical clustering was applied to CGGA datasets for the same goal. This was performed by the Watermelon multisection method [33] that returns WM metric which positively reflects the quality of clustering of samples into pre-defined groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hierarchical clustering of samples from two batches of the CGGA project (CGGA_325 and CGGA_693) showed that samples were clustering by batch ID rather by glioma type (LGG or GBM). This was also quantitatively measured by the Watermelon multisection method [33] that returns WM metric which positively reflects the quality of clustering of samples into pre-defined groups, with WM metrics 0.839 and 0.159 for batchand glioma type clustering, respectively (data not shown).…”
Section: Compatibility Of Glioma Gene Expression Datamentioning
confidence: 99%
“…We observed that Pearson and Spearman correlations for pathway activation levels were statistically significantly higher compared to the single gene expression levels in the same four out of seven cancer types (Figures 4, 5, 9 and 11). For the remaining three cancer types, i.e., hepatocellular carcinoma, ovarian serous cystadenocarcinoma, and uterine corpus endometrial carcinoma, Pearson and Spearman correlations showed poor statistical significance (Figures 6, 8 Paired gene-to-gene and PAL-to-PAL correlation between RNA and protein expression levels estimated within Lung Adenocarcinoma biosamples using Pearson (left) and Spearman (right) correlation coefficients for (A) the total set of genes and molecular pathways; (B) the set of drug target genes and molecular pathways [17].…”
Section: Resultsmentioning
confidence: 99%
“…Victor Tkachev and colleagues [27] discussed sequencing data processing in global machine learning methods in clinical oncology. Marianna Zolotovskaia et al [28] studied molecular heterogeneity of target drugs in oncology.…”
mentioning
confidence: 99%